The Role of Students in Creating Good Democracy and Quality Elections - Ade Putra Ode Amane; Kisman Karinda; Wahyudin Rahman; Wildan Zaman; La Ode Sabirila Jayalangi; Sri Ayu Laali; Haminun Dg. Matorang; Mustakim Ladee; Filo Leonardo Tinggogoy (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This community service activity aims to strengthen students' role in realizing a healthy democracy and quality elections through the dissemination of political education. The methods used include material presentations, discussions, and participatory reflections involving students, academics, and local government. The results of the activity demonstrated an increase in students' understanding of substantive democracy, critical awareness of vote buying practices, and the importance of Pancasila values ​​in political life. Furthermore, this activity strengthened the synergy between universities and the government in improving the political literacy of the younger generation. Students have been proven to have a strategic role as a moral force, social control, and agents of change in encouraging a participatory, transparent, and integrity-based political culture in order to realize a quality democracy.